Cytotoxicity of phosphorus allotropes (black, violet, red) - Naziah Mohamad Latiff (2020)
Black phosphorus has shown great potential in many applications such as energy, optoelectronics and bio/sensing. However, its toxicity study is still in its infancy. Here, the cytotoxicity of black phosphorus prepared by two different synthesis methods, i.e. vapour growth transport and high pressure conversion, are investigated. Precursor and intermediate materials, namely red and violet phosphorus, are also included in this study for a better understanding on the toxicity changes that occurs during the transformation process. We found that the cytotoxicity of phosphorus materials could be influenced by their degree of exfoliation arising from differences in morphology, as well as their extent of oxidation. These findings are important in preparing safe phosphorus materials for real life applications.